2018
DOI: 10.3390/cancers10050153
|View full text |Cite
|
Sign up to set email alerts
|

Eukaryotic Translation Initiation Factor 4A Down-Regulation Mediates Interleukin-24-Induced Apoptosis through Inhibition of Translation

Abstract: Dysregulated activity of helicase eIF4A drives transformation to and maintenance of cancer cell phenotype by reprogramming cellular translation. Interleukin 24 (IL-24) is a tumor-suppressing protein, which has the ability to inhibit angiogenesis, sensitize cancer cells to chemotherapy, and induce cancer cell-specific apoptosis. In this study, we found that eIF4A is inhibited by IL-24. Consequently, selective reduction of translation was observed for mRNAs harboring strong secondary structures in their 5′-untra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…Among all candidate mRNAs, WDR66 has been reported as a human disease‐associated gene (Kim et al, 2012). More important, WDR66 has been uncovered to be a novel oncogene in gastric cancer and involved in the EMT process of esophageal squamous cell carcinoma cells (Wang et al, 2013; Zhong et al, 2018). The present research confirmed that eIF4AIII interacted with WDR66 and further stabilized its mRNA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among all candidate mRNAs, WDR66 has been reported as a human disease‐associated gene (Kim et al, 2012). More important, WDR66 has been uncovered to be a novel oncogene in gastric cancer and involved in the EMT process of esophageal squamous cell carcinoma cells (Wang et al, 2013; Zhong et al, 2018). The present research confirmed that eIF4AIII interacted with WDR66 and further stabilized its mRNA.…”
Section: Discussionmentioning
confidence: 99%
“…They are implicated in certain cellular activities referring to alteration of RNA secondary structure, such as translation initiation, nuclear and mitochondrial splicing, and ribosome and spliceosome assembly. The functional roles of eIF4A family in cancers are exposed in a few studies, for instances, eukaryotic translation initiation Factor 4A silence mediates interleukin‐24‐caused apoptosis by inhibition of translation (Zhong et al, 2018); miR‐133a serves as a tumor suppressor role in colorectal cancer through targeting eIF4A1 (W. Li et al, 2017b); Sanguinarine inhibits the progression of epithelial ovarian cancer by regulating long noncoding RNA (lncRNA) CASC2‐EIF4A3 pathway and/or inhibiting PI3K/AKT/mTOR or nuclear factor kappa B (NF‐κB) signaling pathway (Zhang et al, 2018). The precise function of eIF4AIII in HCC has never been elaborated.…”
Section: Introductionmentioning
confidence: 99%
“…IL24 mRNA is known to have an apoptotic effect on cancer cells but not on noncancer cells [ 22 , 23 ]. IL24 mRNA could induce autophagy as a protective mechanism, while 3-methyladenine (3-MA) inhibition of autophagy significantly enhanced the anticancer effect of IL24 in OSCC [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…34 LY2275796 inhibits the eIF4E complex and its activating kinases, MNK1/2, and is currently in phase 1 development as the second antisense anticancer drug. 35 Inhibition of eIF4A 36 or eIF4F, 37 the catalytic subunits of eIF4F, is shown to lead to apoptosis in selected cancer models. EIF4E, F, and G proteins are involved in tumor progression, angiogenesis, and metastases.…”
Section: Case Study: Ly2275796 and Cyclosporine Combination Therapymentioning
confidence: 99%